A survey of functional dyspepsia in 361, 360 individuals: Phenotypic and genetic cross‐disease analyses. Issue 6 (11th August 2021) - Garcia‐Etxebarria, Koldo; Carbone, Florencia; Teder‐Laving, Maris; Pandit, Anita; Holvoet, Lieselot; Thijs, Vincent; Lemmens, Robin; Bujanda, Luis; Franke, Andre; Zöllner, Sebastian; Boehnke, Michael; Zawistowski, Matthew; et al.
Abstract: Background: Functional dyspepsia (FD) is a common gastrointestinal condition of poorly understood pathophysiology. While symptoms' overlap with other conditions may indicate common pathogenetic mechanisms, genetic predisposition is suspected but has not been adequately investigated. Methods: Using healthcare, questionnaire, and genetic data from three large population‐based biobanks (UK Biobank, EGCUT, and MGI), we surveyed FD comorbidities, heritability, and genetic correlations across a wide spectrum of conditions and traits in 10, 078 cases and 351, 282 non‐FD controls of European ancestry. Key Results: In UK Biobank, 281 diagnoses were detected at increased prevalence in FD, based on healthcare records. Among these, gastrointestinal conditions (OR = 4.0, p  < 1.0 × 10 −300 ), anxiety disorders (OR = 2.3, p  < 1.4 × 10 −27 ), ischemic heart disease (OR = 2.2, p  < 2.3 × 10 −76 ), and infectious and parasitic diseases (OR = 2.1, p  = 1.5 × 10 −73 ) showed strongest association with FD. Similar results were obtained in an analysis of self‐reported conditions and use of medications from questionnaire data. Based on a genome‐wide association meta‐analysis of genotypes across all cohorts, FD heritability was estimated close to 5% ( h SNP 2  = 0.047, p  = 0.014). Genetic correlations indicate FD predisposition is shared with several other diseases and traits (rg  > 0.344), mostly overlapping with those also enriched in FD patients. Suggestive ( p  < 5.0 × 10 −6 ) association with FD risk was detected for 13 loci, with 2 showing nominal replication ( p  < 0.05) in an independent cohort of 192 FD patients. Conclusions & Inferences: FD has a weak heritable component that shows commonalities with multiple conditions across a wide spectrum of pathophysiological domains. This new knowledge contributes to a better understanding of FD etiology and may have implications for improving its treatment. Abstract : FD has a weak heritable component that shows commonalities with multiple conditions across a wide spectrum of pathophysiological domains, including other GI conditions and mood/anxiety disorders.